New Life Through Disaster: A Thematic Analysis of Women's Experiences of Pregnancy and the 2016 Fort McMurray Wildfire - Ashley Pike; Ashley Pike; Cynthia Mikolas; Kathleen Tompkins; Joanne Olson; David M. Olson; Suzette Brémault-Phillips; Suzette Brémault-Phillips (Frontiers Media S.A., 2022)
BackgroundOn May 3, 2016, residents of Fort McMurray Wood Buffalo, Alberta were evacuated due to an uncontrolled wildfire. The short-notice evacuation had destabilizing consequences for residents, including changes in routines, loss of control, and increased uncertainty. These consequences were especially detrimental to women who were pregnant or pre-conception during the evacuation. Pregnant and pre-conception women are particularly susceptible to a vast range of negative consequences during and post natural disasters, including elevated stress and higher incidence of pregnancy complications including gestational diabetes mellitus, pregnancy induced hypertension and C-section. The aim of this study was to understand the experiences, perceived stress and resilience of women who were pregnant during the wildfire. As well as to explore potential interventions to promote the health and enhance resilience of pregnant women and to assist in recovery after exposure to a natural disaster or other traumatic events.MethodsA qualitative thematic analysis of 16 narratives penned by pregnant women and recounted in Ashley Tobin's compilations 93/88,000 and 159 More/ 88,000: Stories of Evacuation, Re-Entry and the In-Between was conducted.ResultsAnalysis revealed five key themes: (1) experience of stress responses due to personal and external factors, (2) social connectedness and support as a facilitator of resilience, (3) performance of resilience-enhancing activities, (4) the roles of pregnancy and motherhood in the experiences of loss and resilience, and (5) the importance of home.ConclusionPregnant women have unique barriers that may negatively impact them during a natural disaster or other form of stressful event. They may benefit from assistance with navigating role transition during pregnancy, training in stress management strategies, and writing interventions to build resiliency and begin the process of recovery from trauma.